The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/prot.25772
|View full text |Cite
|
Sign up to set email alerts
|

Ligand nanovectorization using graphene to target cellular death receptors of cancer cell

Abstract: Tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) is nowadays envisaged as a natural cytokine useful in nanomedicine to eradicate the cancer cells and not the healthy surrounding ones. However, it suffers from cell resistance and strong dispersion in body to prove its efficiency. The understanding at the molecular level of the TRAIL interaction with death receptors (DRs) on cancer cells is thus of fundamental importance to improve its action. We demonstrate here via molecular simulations that TRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Further, molecular docking and molecular dynamics simulations have shown that the adsorption of TRAIL on graphene nanoflakes as a potential cargo is feasible and could lead to the recruitment of the receptors DR4 and DR5 with enhanced efficacy toward the targeted cancer cell. Thus, solid nanoparticles based on graphene flakes are perspective for multiple spatial drug deliveries, including TRAIL protein, due to their form and size [ 31 ].…”
Section: Inorganic Nanoparticles Modified With Trail Pathway-targetin...mentioning
confidence: 99%
“…Further, molecular docking and molecular dynamics simulations have shown that the adsorption of TRAIL on graphene nanoflakes as a potential cargo is feasible and could lead to the recruitment of the receptors DR4 and DR5 with enhanced efficacy toward the targeted cancer cell. Thus, solid nanoparticles based on graphene flakes are perspective for multiple spatial drug deliveries, including TRAIL protein, due to their form and size [ 31 ].…”
Section: Inorganic Nanoparticles Modified With Trail Pathway-targetin...mentioning
confidence: 99%
“…Another form of carbon-based nanoparticles is made from graphene, an allotrope of carbon. A graphenebased co-delivery nanosystem composed of graphene oxide, a PEG linker, and a furin-cleaved peptide encapsulated with TRAIL and doxorubicin (Dox) resulted in the efficient release of TRAIL and Dox to their sites of action by digesting the peptide linker by furin with the increased expression of death receptors in lung and colon adenocarcinoma cells [105] .…”
Section: Carbon-based Nanoparticlesmentioning
confidence: 99%
“…These studies showed that when adsorbed on graphene, TRAIL self-assembling and TRAIL affinities enhanced efficacy towards the targeted cancer cell. TRAIL bound to DR4 and DR5 more effectively when transported by graphene nanoflakes [ 106 ] . The synthesis of a novel nanohybrid system, sTRAIL (TRAIL fused with crystalline bacterial cell surface layer (S layer) protein), combined with graphene quantum dots or GQDs elevated the functional stability of TRAIL by improving pro-caspase-8 activation and mitochondria-dependent cell death in doxorubicin-pretreated human colon cancer cells (HT-29) when compared to S-TRAIL alone.…”
Section: Nanoparticle-based Drug and Gene Delivery Systemsmentioning
confidence: 99%
“…A variety of nanocarriers, including metallic NPs [ 134 , 135 , 136 ], polymeric NPs [ 137 , 138 , 139 , 140 ], lipid-based NPs [ 141 , 142 , 143 ], protein NPs [ 128 , 144 , 145 , 146 ] and carbon-based NPs [ 132 , 147 ], have been tested as TRAIL carriers. Key findings of these studies are summarized in Figure 3 .…”
Section: Trail Formulations To Mimic Membrane-bound Trailmentioning
confidence: 99%